2020
DOI: 10.1002/jbm.a.37095
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐containing bioactive glass mimics vascular endothelial growth factor A and hypoxia inducible factor 1 function

Abstract: Bioactive glasses (BGs) have shown great potential for tissue regeneration and their composition flexibility allows the incorporation of different ions with physiological activities and therapeutic properties in the glass network. Among the many ions that could be incorporated, cobalt (Co) is a significant one, as it mimics hypoxia, triggering the formation of new blood vessels by the vascular endothelial growth factor A (VEGFA), due to the stabilizing effect on the hypoxia inducible factor 1 subunit alpha (HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Cu 2+ and Co 2+ can promote angiogenesis by contributing to a hypoxic microenvironment and increasing the expression of HIF-α . 109–113 More impressively, Bosch-Rué et al 226 demonstrated that Co 2+ significantly improved the capacity of HUVECs to form tubular structures. Although Fe 3+ still has strong pro-angiogenic effects, 227 its relatively high cytotoxicity and the oxidative damage it causes limit its further application.…”
Section: Regulating Bone Metabolism With Metal Ionsmentioning
confidence: 99%
“…Cu 2+ and Co 2+ can promote angiogenesis by contributing to a hypoxic microenvironment and increasing the expression of HIF-α . 109–113 More impressively, Bosch-Rué et al 226 demonstrated that Co 2+ significantly improved the capacity of HUVECs to form tubular structures. Although Fe 3+ still has strong pro-angiogenic effects, 227 its relatively high cytotoxicity and the oxidative damage it causes limit its further application.…”
Section: Regulating Bone Metabolism With Metal Ionsmentioning
confidence: 99%
“…If cobalt ion is released rapidly and extensively in situ, this ion can cause the death of cancer cells by ferroptosis. 120,[123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] Ferroptosis is generally a type of cell death caused by ROS accumulation due to Fenton's or Fenton-like reactions. 120,[139][140][141] On the other hand, we cannot ignore that cobalt has a potent pro-angiogenic effect, which could contribute to cancer development, thus achieving an opposite effect.…”
Section: Drug and Ion Deliverymentioning
confidence: 99%
“…Low and suitable concentrations of cobalt ions can cause angiogenesis during tissue regeneration due to their hypoxia‐mimetic effect. If cobalt ion is released rapidly and extensively in situ, this ion can cause the death of cancer cells by ferroptosis 120,123–138 . Ferroptosis is generally a type of cell death caused by ROS accumulation due to Fenton's or Fenton‐like reactions 120,139–141 .…”
Section: Drug and Ion Deliverymentioning
confidence: 99%
“…Cobalt-containing borate glasses also increased HIF-1α, VEGF protein secretion, ALP activity in hBMSC culture (Deng et al, 2019). Cobalt was also incorporated into silicate based sol-gel glass (Barrioni et al, 2018a;Barrioni et al, 2018b;Kermani et al, 2020), provoking VEGF expression from fibroblasts (Dziadek et al, 2018) and HUVECs (de Laia et al, 2021), and into inorganic/organic hybrid scaffolds (de Laia et al, 2020). Interestingly, the original 45S5 Bioglass composition has also been shown increase the expression of VEGF in fibroblasts (Day et al, 2004;Day, 2005;Gorustovich et al, 2010;Gerhardt et al, 2011) and endothelial cells (Leu and Leach, 2008) at specific concentrations.…”
Section: Introductionmentioning
confidence: 99%